Space, Time, and Causality - Polkinghorne, John C. (Zygon, 2006)
Abstract. The characters of space, time, and causality are issues that are constrained by physics but that require also acts of metaphysical decision. Relativity theory is consistent both with the idea of an a temporal block universe and with a temporal universe of true becoming. Science's account of causal properties is patchy and does not imply the closure of the universe to other forms of causal influence. Intrinsic unpredictabilities offer opportunities for metaphysical conjecture concerning the form that such additional causal principles might take. Different theological understandings of how God relates to time afford legitimate criteria for differing metaphysical decisions about the nature of temporality.